Tawḥīd Ḥākimiyyah Verses In Ibn ‘Āshūr’s Interpretation - Saifuddin Herlambang Munthe (ILMU USHULUDDIN, 2018)
This paper discusses Ibn 'Āshūr's interpretation of the verses which serve as the basis of the Tawḥīd ḥākimiyyah concept. Despitebeing an expert in Islamic law, Ibn ‘Āshūr did not perceive the Tawḥīd ḥākimiyyah verses as a basis for the necessity to apply Shari'a law at the level of government. Perhaps the thought of "hākimiyyatullāh" had not developed in the time of Ibn 'Āshūr. Another reason, Ibn ‘Āshūr used a linguistic-sociological contextual approach when interpreting the verses claimed to be the basis of the Tawḥīd ḥākimiyyah concept. With this approach, Ibn ‘Āshūr did not use the Tawḥīd ḥākimiyyah verse to judge the behavior of the Muslims because in fact these verses were revealed to explain the behavior of the polytheists who opposed Islamic da'wah.